2019
DOI: 10.1108/ijccsm-07-2017-0145
|View full text |Cite
|
Sign up to set email alerts
|

Understanding community vulnerability to climate change and variability at a coastal municipality in southern Mozambique

Abstract: Purpose -This paper aims to understand the vulnerability of community livelihoods (human, social, financial, natural and physical assets) at a coastal environment in southern Mozambique, considering the level of exposure, sensitivity and adaptive capacity to climate change.Design/methodology/approach -The study adopted the sustainable livelihoods approach. Data were collected through distribution of a structured questionnaire to 476 randomly selected households at the municipality of Inhambane. The questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 62 publications
3
20
0
Order By: Relevance
“…According to Allison and Ellis (2001), the SLA framework originated from studies that were concerned with understanding how rural poor populations manage natural disasters such as floods, droughts, animal pests and diseases. Zacarias (2019) asserts that the SLA framework depicts the livelihood assets, the external factors that affect the livelihoods, institutions and processes and the outcomes of the livelihood activities and strategies and the relationships between them. The SLA framework has been successfully used in numerous studies related to rural livelihoods and food security (Ansoms and McKay, 2010; Xu et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…According to Allison and Ellis (2001), the SLA framework originated from studies that were concerned with understanding how rural poor populations manage natural disasters such as floods, droughts, animal pests and diseases. Zacarias (2019) asserts that the SLA framework depicts the livelihood assets, the external factors that affect the livelihoods, institutions and processes and the outcomes of the livelihood activities and strategies and the relationships between them. The SLA framework has been successfully used in numerous studies related to rural livelihoods and food security (Ansoms and McKay, 2010; Xu et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Similar to the current study, the underlying causes of vulnerability in the Savanna Ecosystem in Ghana were socio economic factors. Zacarias (2019), in his quest to understand community vulnerability to climate change and variability at a coastal municipality in southern Mozambique found out that vulnerability is susceptibility driven and is especially derived from susceptibilities of physical, financial and social capitals. Comparably, Ahmadalipour et al (2019) found out that vulnerability to drought is specifically high in the Sub Saharan countries than the Sahel region despite the latter being an area of high water stress.…”
Section: Discussionmentioning
confidence: 99%
“…It is susceptibility driven rooted in social, economic and largely, environmental factors. Measurement of vulnerability to single natural hazards including floods and droughts has been conducted in Sub-Saharan Africa (Ahmadalipour & Moradkhani, 2018;Mwale et al, 2015;Williams et al, 2018;Zacarias, 2019). More importantly, a coupled IPCC and UNISDR framework has been applied tested on floods (Mwale et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Investment in structural resources to improve hazard-dependent variables, such as the material of houses and sanitation systems, can help to lessen the impacts of cyclones and floods, so reducing vulnerability levels to coastal hazards (e.g. Mazumdar and Paul 2016;Zacarias 2019). Here, the SVI was used as a means to identify large differences between districts and provinces and provide the socioeconomic component to the IVCC.…”
Section: Limitationsmentioning
confidence: 99%
“…Arkema et al 2013). The application of such indices is very limited in EA, often focusing on social vulnerability at the local or district level (Hahn et al 2009;Zacarias 2019). Cabral et al (2017) calculated an index of exposure to coastal hazards for Mozambique considering the effect of coastal habitats.…”
Section: Introductionmentioning
confidence: 99%